Mobile Robot Coordination and navigation with directional antennas in positionless Wireless Sensor Networks. (24th June 2011) - Jiang, Jehn-Ruey; Lai, Yung-Liang; Deng, Fu-Cheng
Three schemes are proposed to coordinate and navigate mobile robots with directional antennas in a positionless wireless sensor network for the purpose of emergency rescue. The k-farthest-node forwarding scheme is for Waiting-for-Rescue (WFR) nodes to broadcast packets to ask mobile robots to come to help. The Mobile Robot Coordination (MRC) is to coordinate multiple mobile robots so that each WFR node is associated one nearby mobile node which is navigated by the Tree Assisted Navigation (TAN) scheme to fast reach the WFR node. The schemes' effectiveness is verified by the ns-2 simulator.